Pembrolizumab in classical Hodgkin's lymphoma. (30th May 2016) - Maly, Joseph; Alinari, Lapo
Abstract: Pembrolizumab is a humanized monoclonal antibody directed against programmed cell death protein 1 (PD‐1), a key immune‐inhibitory molecule expressed on T cells and implicated in CD4+ T‐cell exhaustion and tumor immune‐escape mechanisms. Classical Hodgkin's lymphoma (cHL) is a unique B‐cell malignancy in the sense that malignant Reed–Sternberg (RS) cells represent a small percentage of cells within an extensive immune cell infiltrate. PD‐1 ligands are upregulated on RS cells as a consequence of both chromosome 9p24.1 amplification and Epstein–Barr virus infection and by interacting with PD‐1 promote an immune‐suppressive effect. By augmenting antitumor immune response, pembrolizumab and nivolumab, another monoclonal antibody against PD‐1, have shown significant activity in patients with relapsed/refractory cHL as well as an acceptable toxicity profile with immune‐related adverse events that are generally manageable. In this review, we explore the rationale for targeting PD‐1 in cHL, review the clinical trial results supporting the use of checkpoint inhibitors in this disease, and present future directions for investigation in which this approach may be used.